Beispiel Nr: 28
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 2 x +5 y =7\\ -4 x +2 y = -6 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 2 x +5 y =7\\ II \qquad -4 x +2 y = -6 \\ \text{I nach y auflösen}\\ 2 x +5 y =7 \\ 2 x +5 y =7 \qquad /-2 x\\ 5 y =7 -2 x \qquad /:5 \\ y =1\frac{2}{5} -\frac{2}{5} x \\ \text{II nach y auflösen}\\ -4 x +2 y =-6 \\ -4 x +2 y =-6 \qquad /+4 x\\ 2 y =-6 +4 x \qquad /:2 \\ y =-3 +2 x \\ \text{I = II}\\ 1\frac{2}{5} -\frac{2}{5} x =-3 +2 x \qquad /+\frac{2}{5} x /+3 \\ 1\frac{2}{5}+3 =2 x +\frac{2}{5} x \\ 4\frac{2}{5} =2\frac{2}{5} x \qquad /:2\frac{2}{5} \\ x=1\frac{5}{6} \\ \text{x in I}\\ y =1\frac{2}{5} -\frac{2}{5} \cdot 1\frac{5}{6} \\ y=\frac{2}{3} \\ L=\{1\frac{5}{6}/\frac{2}{3}\} \end{array} & \begin{array}{l} I \qquad 2 x +5 y =7\\ II \qquad -4 x +2 y = -6 \\ \text{I nach x auflösen}\\ 2 x +5 y =7 \\ 2 x +5 y =7 \qquad /-5 y\\ 2 x =7 -5 y \qquad /:2 \\ x =3\frac{1}{2} -2\frac{1}{2} y \\ \text{II nach x auflösen}\\ -4 x +2 y =-6 \\ -4 x +2 y =-6 \qquad /-2 y\\ -4 x =-6 -2 y \qquad /:\left(-4\right) \\ x =1\frac{1}{2} +\frac{1}{2} y \\ \text{I = II}\\ 3\frac{1}{2} -2\frac{1}{2} y =1\frac{1}{2} +\frac{1}{2} y \qquad /+2\frac{1}{2} y /-1\frac{1}{2} \\ 3\frac{1}{2}-1\frac{1}{2} =\frac{1}{2} y +2\frac{1}{2} y \\ 2 =3 y \qquad /:3 \\ y=\frac{2}{3} \\ \text{y in I}\\ x =3\frac{1}{2} -2\frac{1}{2} \cdot \frac{2}{3} \\ x=1\frac{5}{6} \\ L=\{1\frac{5}{6}/\frac{2}{3}\} \end{array} \end{array} $